2007
DOI: 10.1021/ct700072a
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional and Semiempirical Molecular Orbital Methods Including Dispersion Corrections for the Accurate Description of Noncovalent Interactions Involving Sulfur-Containing Molecules

Abstract: We describe the use of density functional theory (DFT-D) and semiempirical (AM1-D and PM3-D) methods having an added empirical dispersion correction, to treat noncovalent interactions between molecules involving sulfur atoms. The DFT-D method, with the BLYP and B3LYP functionals, was judged against a small-molecule database involving sulfur-π, S-H···S, and C-H···S interactions for which high-level MP2 or CCSD(T) estimates of the structures and binding or interaction energies are available. This database was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 43 publications
5
86
0
Order By: Relevance
“…The 60 complexes we used for the fitting of the parameters are presented in table 1, in which the dispersion-including binding energies as obtained with ONETEP are given using the optimized parameters for the three damping functions (DF1, DF2 and DF3) and the PBE (Hammer et al 1999) (Jurečka et al 2006;Morgado et al 2007). We can observe from table 1 that the inclusion of the dispersion contribution dramatically improves the binding energies, in most cases leading to an agreement with the literature results that is better than 1 kcal mol K1 .…”
Section: Resultsmentioning
confidence: 99%
“…The 60 complexes we used for the fitting of the parameters are presented in table 1, in which the dispersion-including binding energies as obtained with ONETEP are given using the optimized parameters for the three damping functions (DF1, DF2 and DF3) and the PBE (Hammer et al 1999) (Jurečka et al 2006;Morgado et al 2007). We can observe from table 1 that the inclusion of the dispersion contribution dramatically improves the binding energies, in most cases leading to an agreement with the literature results that is better than 1 kcal mol K1 .…”
Section: Resultsmentioning
confidence: 99%
“…65,66 More pertinent to our study is the recent use of the B3LYP-D functional to accurately calculate noncovalent interactions between molecules containing sulfur atoms. 67 To supplement these extensive studies (which focused on only molecular complexes), we also performed additional calculations on bulk organic molecular crystals with noncovalent interactions similar to the nanotubes in our study. Fortunately, the recent publication of full ab initio cohesive energies for oligothiophenes by Nabok et al 57 provides an excellent benchmark comparison with our B3LYP-D results.…”
Section: A Benchmark Calculationsmentioning
confidence: 99%
“…20,21,[25][26][27] Theoretical studies on heterocyclization reactions indicated that the activation energies as well as properties of stationary points were in a good agreement with the experimental results if the B3LYP hybrid functional at the DFT was used for the calculation. [28][29][30][31][32][33] An attempt to choose basis sets 6-311++G(d, p), 6-31+G(d), 6-31G(d, p) and 6-31G(d) for evaluation reactions of heterocyclic systems with heavy atoms revealed that all basis sets provided almost identical results. 9,34-37 Thus, we chose 6-31+G(d, p) basis set as the best compromise between speed and accuracy for the investigation of the acylation-cyclization reaction.…”
Section: Theoretical Studiesmentioning
confidence: 99%